2020
DOI: 10.1093/tbm/ibaa039
|View full text |Cite
|
Sign up to set email alerts
|

Content analysis of behavior change techniques in maternal and infant health apps

Abstract: Maternal and infant health (MIH) mobile applications (apps) are increasingly popular and frequently used for health education and decision making. Interventions grounded in theory-based behavior change techniques (BCTs) are shown to be effective in promoting healthy behavior changes. MIH apps have the potential to be useful tools, yet the extent to which they incorporate BCTs is still unknown. The objective of this study was to assess the presence of BCTs in popular MIH apps available in the Apple App and Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Johnson & Johnson's BabyCenter website and mobile app provide valuable resources and information for expectant and new parents, including pregnancy tracking tools, baby development guides, and parenting advice. The platform leverages content marketing, email marketing, and community engagement to build brand loyalty and trust among parents (Biviji et al, 2021).…”
Section: Case Studies and Practical Examplesmentioning
confidence: 99%
“…Johnson & Johnson's BabyCenter website and mobile app provide valuable resources and information for expectant and new parents, including pregnancy tracking tools, baby development guides, and parenting advice. The platform leverages content marketing, email marketing, and community engagement to build brand loyalty and trust among parents (Biviji et al, 2021).…”
Section: Case Studies and Practical Examplesmentioning
confidence: 99%
“…The studies included could be sorted into 8 main prevention and child health promoting topics: parental feeding and nutrition (n=19) [43,45,47,48,[51][52][53][55][56][57][58][59][60][61][72][73][74]82,86], physical activity (n=8) [43][44][45][46][47][48][49]84], maternal-child health (n=6) [44,45,65,67,75,85], parent-child health (n=5) [66,68,78,79,83], healthy environment (n=3) [69][70][71], dental health (n=2) [62,63], mental health (n=1) [66], and sleep (n=1) [64]. A crossover of these inductively derived topics occurred in some studies and these were not mutually exclusive; if a study descriptively included more than 1 topic, then the study was included in both topics.…”
Section: Broad Topicsmentioning
confidence: 99%
“…In this context, health apps may offer an under-utilised solution for supporting lifestyle changes and allowing self-monitoring during pregnancy (10) . Self-monitoring is a behavioral change technique, based on a social cognitive theory of self-regulation (11) , widely incorporated into health apps (12)(13)(14) . Previous studies, although with relatively small sample sizes, have found that health technology may offer a useful approach for self-monitoring and can provide encouragement in adopting a health-promoting lifestyle during pregnancy.…”
Section: Introductionmentioning
confidence: 99%